Synthesis, characterization and photophysical properties of cyclotriphosphazenes including heterocyclic rings - Ibisoglu, Hanife; Erdemir, Eda; Atilla, Devrim; Zorlu, Yunus; Senkuytu, Elif (Elsevier Science Sa, 2019)
In the present work, new cyclotriphosphazene derivatives, {[N3P3(biph)(R)(4)] (biph = 2',2''-dioxy-1',1''-bi-phenyl, R = imidazolyl (5) and benzimidazolyl (7)}, were synthesized for the first time. Both of these compounds (5 and 7) were fully characterized by elemental analysis, mass spectrometry and H-1 and P-31 NMR spectroscopy. The crystal structures of compounds 5 and 7 were determined by single-crystal X-ray crystallography. Furthermore, a second polymorph (triclinic form) of 2,2-monospiro-(2',2''-dioxy-1',1''-biphenyl)-4,4,6,6-tetrachlorocyclotriphosphazene (3) was isolated during the course of our study. UV-Vis absorption and fluorescence emission properties of 3, 5 and 7 were determined in a range of different solvents.
Keywords: Cyclophosphazene; Imidazole; 2,2'-Dihydroxybiphenyl; Benzimidazole; Photophysical properties